Gambaran self-disclosure pada perempuan pengguna aplikasi online dating Tinder di tengah pandemi COVID-19 - Salsabila, Firnandha; Widiasavitri, Putu Nugrahaeni (Jurnal Psikologi Udayana, 2021)
Technological developments have made it possible for women to find mates online. One application that makes it possible to find matches online is Tinder. The emergence of the COVID-19 pandemic has led to an increase in Tinder users and increased conversation duration. This increase was motivated by the boredom that was felt during the implementation of the PSBB. Proper self-disclosure is necessary so that communication runs smoothly and builds good relationships. This study aims to get an overview of self-disclosure among women users of online dating application Tinder during the COVID-19 pandemic by using a qualitative research method with a case study approach. In this study, respondents were five women who were active users of the Tinder online dating application during the COVID-19 pandemic. Data collection using interviews. The results showed that self-disclosure in women could be seen through several things: the limitations of communicating, the factors that influence the swiping process, and the Tinder bio's information.